SIS: a program to generate draft genome sequence scaffolds for prokaryotes - Dias Zanoni; Dias Ulisses; Setubal João C (BMC Bioinformatics, 2012)
Abstract Background Decreasing costs of DNA sequencing have made prokaryotic draft genome sequences increasingly common. A contig scaffold is an ordering of contigs in the correct orientation. A scaffold can help genome comparisons and guide gap closure efforts. One popular technique for obtaining contig scaffolds is to map contigs onto a reference genome. However, rearrangements that may exist between the query and reference genomes may result in incorrect scaffolds, if these rearrangements are not taken into account. Large-scale inversions are common rearrangement events in prokaryotic genomes. Even in draft genomes it is possible to detect the presence of inversions given sufficient sequencing coverage and a sufficiently close reference genome. Results We present a linear-time algorithm that can generate a set of contig scaffolds for a draft genome sequence represented in contigs given a reference genome. The algorithm is aimed at prokaryotic genomes and relies on the presence of matching sequence patterns between the query and reference genomes that can be interpreted as the result of large-scale inversions; we call these patterns inversion signatures. Our algorithm is capable of correctly generating a scaffold if at least one member of every inversion signature pair is present in contigs and no inversion signatures have been overwritten in evolution. The algorithm is also capable of generating scaffolds in the presence of any kind of inversion, even though in this general case there is no guarantee that all scaffolds in the scaffold set will be correct. We compare the performance of <smcaps>sis</smcaps>, the program that implements the algorithm, to seven other scaffold-generating programs. The results of our tests show that <smcaps>sis</smcaps> has overall better performance. Conclusions <smcaps>sis</smcaps> is a new easy-to-use tool to generate contig scaffolds, available both as stand-alone and as a web server. The good performance of <smcaps>sis</smcaps> in our tests adds evidence that large-scale inversions are widespread in prokaryotic genomes.